HUBUNGAN MANAJEMEN WAKTU PADA PRESTASI BELAJAR MAHASISWA AKUNTANSI YANG BEKERJA DAN MAHASISWA AKUNTANSI TIDAK BEKERJA - Manalu, Atma Retina; Haposan Banjarnahor (SCIENTIA JOURNAL, 2022)
This study aims to determine whether time management, academic achievement, is related to accounting students who work and do not work. In this study, the population was 7th semester accounting study program students in the city of Batam. The population in this study was 783 respondents and then a sample of 100 respondents was obtained by using the slovin formula for sampling. Data collection techniques using questionnaires and observation. Data analysis techniques were carried out by analyzing the validity test and reliability test, classic assumption test, hypothesis testing, coefficient of determination test (R2). The results of the t test analysis partially time management are not related to accounting students who work and do not work. Learning achievement is positively related to working and non-working accounting students. Simultaneously time management, academic achievement, to accounting students who work and do not work are not significantly related. The result of the coefficient of determination is 4.9%, meaning that the independent variables influence the dependent variable sufficiently. Keywords: Time management, academic achievement, working and non-working accounting students.